"Be Real Black for Me": The Icon, Idol, and Incarnation of America's First Black President. Issue 1 (2nd January 2018) - Floyd-Thomas, Stacey M.
ABSTRACT: This article explores the manner in which the Obama presidency, as generated presentation and interrogation of Blackness, was meant to reify Blackness and fix it in ways that generate Black hope and White hate. It explores the manner in which Obama has come to both symbolize and challenge notions of Blackness across the political and racial divide in the U.S.A. wherein White supremacy has become God and acquiescing to it has become our religion.